The Deliverance of Others : Reading Literature in a Global Age - Palumbo-Liu, David (Book collections on Project MUSE., 2012)
The distinguished literary critic David Palumbo-Liu posits reading literature as an ethical act, a way of thinking through our relations to others in the age of globalization.